T Cell Responses Induced by DNA Vaccines Based on the DENV2 E and NS1 Proteins in Mice: Importance in Protection and Immunodominant Epitope Identification - Pinto, Paolla B. A.; Assis, Maysa L.; Vallochi, Adriana L.; Pacheco, Agatha R.; Lima, Lauro M.; Quaresma, Kátia R. L.; Pereira, Bernardo A. S.; Costa, Simone M.; Alves, Ada M. B. (Frontiers in Immunology, 2019)
The importance of the cellular immune response against DENV has been increasingly highlighted in the past few years, in particular for vaccine development. We have previously constructed two plasmids, pE1D2 and pcTPANS1, encoding the envelope (E) ectodomain (domains I, II and III) and the non-structural 1 (NS1) protein of dengue virus serotype 2 (DENV2), respectively. In the present work, we analyzed the induction of the cellular response in mice immunized with these DNA vaccines and identified the immunogenic peptides. Vaccinated BALB/c mice became protected against a lethal challenge of DENV2. Depletion of CD4+ cells in vaccinated animals almost completely abolished protection elicited by both vaccines. In contrast, a significant number of pE1D2- and pcTPANS1-immunized mice survived virus challenge after depletion of CD8+ cells, although some animals presented morbidity. To identify immunogenic peptides recognized by T cells, we stimulated splenocytes with overlapping peptide libraries covering the E and NS1 proteins and evaluated the production of IFN-γ by ELISPOT. We detected two and three immunodominant epitopes in the E and NS1 proteins, respectively, and four additional NS1-derived peptides after virus challenge. Characterization by intracellular cytokine staining (ICS) revealed that both CD4+ and CD8+ T cells were involved in IFN-γ and TNF-α production. The IFN-γ ICS confirmed reaction of almost all E-derived peptides before challenge and identified other epitopes after infection. All NS1-derived peptides were able to elicit IFN-γ production in CD4+ cells, while only a few peptides induced expression of this cytokine in CD8+ T lymphocytes. Interestingly, we observed an increase in the frequency of either CD4+ or CD8+ T cells producing TNF-α after immunization with the pE1D2 and challenge with DENV2, while lymphocytes from pcTPANS1-vaccinated animals maintained ordinary TNF-α production after virus infection. We also assessed the recognition of E and NS1 immunogenic peptides in C57BL/6 mice due to the difference in MHC haplotype expression. Two NS1-derived epitopes featured prominently in the IFN-γ response with cells from both animal strains. Overall, our results emphasize the importance of the T cell response involved in protection against dengue induced by E and NS1 based DNA vaccines.